2015
DOI: 10.2169/internalmedicine.54.4474
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Pleomorphic Carcinoma of the Lung Harboring an Anaplastic Lymphoma Kinase (ALK) Rearrangement

Abstract: Molecular testing for anomalies, such as epidermal growth factor receptor mutations and anaplastic lymphoma kinase (ALK) rearrangement, is part of the current standard of care for non-small cell lung cancer, particularly adenocarcinoma. ALK rearrangement occurs most frequently in adenocarcinoma cells and rarely in non-adenocarcinoma cells. We herein report a rare case of pleomorphic lung carcinoma with ALK rearrangement in both its adenocarcinoma and spindle cell components. This case suggests the possibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(13 reference statements)
2
2
0
Order By: Relevance
“…Both previous reports and our present study revealed that ALK rearrangement is more likely to be detected in PSCs with adenocarcinoma components of younger never-smoked patients [12], [13], [14]. Another intriguing observation we found involves two patients with carcinosarcoma harboring ALK rearrangement.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Both previous reports and our present study revealed that ALK rearrangement is more likely to be detected in PSCs with adenocarcinoma components of younger never-smoked patients [12], [13], [14]. Another intriguing observation we found involves two patients with carcinosarcoma harboring ALK rearrangement.…”
Section: Discussionsupporting
confidence: 80%
“…Previously, almost all of the studies using a small sample size have reported that no ALK rearrangement occurred in PSC [10], [11]. Recently, a few cases of ALK rearrangement-positive PSC have been reported in Japan [12], [13], [14]. In our large sample study, the incidence rate of ALK rearrangement in PSC was 3.5%, which is similar to the frequency in typical NSCLC.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Other studies describe three patients aged 50, 69, and 87 years with PPC with ALK rearrangements. 12 14 These findings suggest that ALK-positive PPC patients may be older than patients with ALK-positive lung adenocarinoma. 10 Moreover, it is notable that the epithelial components of our patients and those of the three aforementioned patients were all adenocarcinomas, consistent with the findings of Chen et al 15 that 4 of 5 ALK-positive patients with PSC had adenocarcinomas with epithelial components.…”
Section: Discussionmentioning
confidence: 91%